Design of a low-cost elutrition system for separation of raw conilon coffee beans of different diameters - Freires, Thales Amaral; Bento, Nícholas Alexandre Berger; Soares, Vinícius Barroso; Porto, Paulo Sergio da Silva (Brazilian Journal of Production Engineering, 2025)
Coffee processing aims to produce more homogeneous batches that meet commercialization and industrial standards. Considering the limitations of small producers, a low-cost multistage elutriator was designed. Each stage was composed of plastic tubes with diameters of 50, 75, and 100 mm, connected in series from the smallest to the largest. The separation of raw conilon coffee beans was evaluated using air as the transport fluid. Initial characterization indicated particle diameters between 0.60 and 0.93 cm. No correlation was observed between diameter and specific mass, nor between specific mass and terminal velocity. This behavior may be associated with variations in sphericity. Terminal velocity showed an inverse linear relationship with particle diameter. At an elutriation velocity of 713.13 cm·s⁻¹, more than 87% of the smaller beans were recovered. Material transported to the remaining stages of the system was considered defective.
Keywords: Elutriator; Conilon Coffee; Modeling